Nanoobjects formed by ionic PAMAM dendrimers: hydrophilic/lipophilic modulation and encapsulation properties1. Issue 30 (14th August 2015) - Fedeli, E.; Hernández-Aínsa, S.; Lancelot, A.; González-Pastor, R.; Calvo, P.; Sierra, T.; Serrano, J. L.
<x xml:space="preserve">Abstract</x> The HLB of ionic-PAMAM codendrimers determines the mesomorphism, the aggregation in water, the cytotoxicity and the encapsulation of a lipophilic drug.